Diagnosis of training for badminton coaches of sports initiation in Pinar del Río, Cuba - Ayrán Arencibia Moreno; Maidelin Díaz Miranda; Margelia Barbara Ramirez Blanco; Laly Viviana Cedeño Sánchez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2018)
This research shows the inadequacies in the training of the Badminton trainers of the province of Pinar del Río, starting from the characteristics of their preparation, defining their needs and establishing their possible solution to eliminate the insufficiencies in their knowledge. That is why they use theoretical and empirical methods such as the historical-logical, the analysis-synthesis, the induction-deduction, the observation, interview, as well as the percentage analysis. Based on the results of the diagnosis, the training needs of these trainers were determined, which will allow the subsequent design and execution of an improvement program to respond to these needs, thus contributing to the overcoming of this technical force, in for superior results.